NAD: Not just a pawn on the board of plant-pathogen interactions - Pétriacq, Pierre (Landes Bioscience, 2013)
Many metabolic processes that occur in living cells involve oxido-reduction (redox) chemistry underpinned by redox compounds such as glutathione, ascorbate and/or pyridine nucleotides. Among these redox carriers, nicotinamide adenine dinucleotide (NAD) is the cornerstone of cellular oxidations along catabolism and is therefore essential for plant growth and development. In addition to its redox role, there is now compelling evidence that NAD is a signal molecule controlling crucial functions like primary and secondary carbon metabolism. Recent studies using integrative -omics approaches combined with molecular pathology have shown that manipulating NAD biosynthesis and recycling lead to an alteration of metabolites pools and developmental processes, and changes in the resistance to various pathogens. NAD levels should now be viewed as a potential target to improve tolerance to biotic stress and crop improvement. In this paper, we review the current knowledge on the key role of NAD (and its metabolism) in plant responses to pathogen infections.